Tomato plant extract (Lycopersicon esculentum) obtained from agroindustrial byproducts and its antifungal activity against Fusarium spp. - Isidro-Requejo, Luis M.; Márquez-Ríos, Enrique; Del Toro-Sánchez, Carmen L.; Ruiz-Cruz, Saúl; Valero-Garrido, Daniel; Suárez-Jiménez, Guadalupe M. (Frontiers in Sustainable Food Systems, 2023)
Phytopathogenic fungi are a constant danger in the production of different crops around the world, especially in melons, since they can cause significant economic losses during the harvest, affecting the quality and shelf life. In recent years, producers have increasingly used chemical pesticides indiscriminately, causing environmental problems and damage to public health. For this reason, phytopathogenic fungi become more resistant. However, it is essential to guarantee the safety, quality, and shelf life of food after harvest, during transportation, storage and marketing. The presence of fungi in food can cause diseases transmitted through the production of toxins. Most producers depend on the discriminated use of chemical pesticides, which is a great challenge to guarantee food safety and sustainable agricultural production. To solve this problem, some extracts derived from tomato plants after harvest containing bioactive compounds have been implemented. These compounds can be natural antifungal agents as they contain phenols, flavonoids, and vitamins. Bioactive compounds emerge as a sustainable and safe opportunity in the search for new antifungal and antimicrobial agents. Therefore, the objective of this study was to determine the in vitro antifungal activity of whole tomato plant extracts on three phytopathogenic fungi. The research findings indicated that a concentration of 74.7 μg/mL of TPE resulted in a complete inhibition of mycelial growth in Fusarium oxysporum, Fusarium graminearum, and Fusarium verticillioides. Additionally, TPE exhibited both fungistatic and fungicidal effects on these Fusarium species, with a MIC50 of 30.7, 31.5, and 29.5, and a MFC of 82.4, 78.6, and 75.8 μg/mL, respectively. As a result, this study suggests that TPE can be considered as an environmentally friendly solution for extracting tomato plants, which can be applied to the surface of whole fruits or incorporated into semi-processed foods.